Daphnia inhibits the emergence of spatial pattern in a simple consumer–resource system. Issue 4 (3rd April 2017) - Betini, Gustavo S.; Avgar, Tal; McCann, Kevin S.; Fryxell, John M.
Abstract: Spatial self‐organization can occur in many ecosystems with important effects on food web dynamics and the maintenance of biodiversity. The consumer–resource interaction is known to generate spatial patterning, but only a few empirical studies have investigated the effect of the consumer on resource distribution. Here we report results from a large aquatic mesocosm experiment used to investigate the effect of the consumer Daphnia magna on the distribution of its resource, the green algae Chlorella vulgaris . We maintained large tanks with capacity for 26 , 000 L with either algae or both algae and Daphnia in different temperature conditions. We found that the presence of D. magna inhibited spatial structure in algal distribution that arose as a consequence of increasing temperature. We conjecture that this homogenization effect might be caused by a combination of high mobility combined with high rates of algal consumption by Daphnia . Our study emphasizes the importance of both local constraints on growth and behavioral responses in either promoting or suppressing spatial self‐organization in natural populations.